THE EFFECT OF INCOME LEVEL, KNOWLEDGE, TAXPAYER AWARENESS AND TAX OFFICER SERVICES ON COMPLIANCE WITH PAYING LAND AND BUILDING TAXES IN PASAR REBO SUBDISTRICT, EAST JAKARTA - Arnoldus Christo Novrianto; Nurul Aisyah Rachmawati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
This study aims to find out the influence of income levels, knowledge, taxpayer awareness and tax officer services on the compliance of paying land and building taxes. The population of this research includes the taxpayers of the land and buildings located in the city of East Jakarta, especially in Pasar Rebo District. Questionnaires obtained after being distributed to respondents amounted to 110. This research uses quantitative approach and uses structural model analysis (SEM). This research also uses hypothesis testing in the form of z test. The results shows that the level of knowledge has no effect on taxpayer compliance while the level of income, awareness and service of tax officers has a positive effect on taxpayer compliance.